Reasons for ordering spinal x-ray investigations: How they influence general practitioners’ management - Houben, P.H.H. (College of Family Physicians of Canada, 2006)
OBJECTIVE: To explore whether general practitioners who request spinal x-ray investigations are less likely to refer, prescribe medication, or order additional tests when they intend only to reassure patients rather than to exclude or confirm disease. DESIGN: Cross-sectional survey. Physicians recorded reasons for requesting x-ray examinations and differential diagnoses on the request form. When they received a radiologist’s report on a spinal x-ray test, GPs also received a questionnaire on their subsequent management. SETTING: Maastricht region of the Netherlands. PARTICIPANTS: All 90 GPs in the Maastricht region who referred patients for spinal x-ray examinations during 19 consecutive weeks. MAIN OUTCOME MEASURES: Reason for requesting spinal x-ray investigations, results, and subsequent management. RESULTS: We received completed questionnaires on 386 patient contacts. Physicians were significantly less likely to refer, prescribe medication, or order additional tests when they intended only to reassure patients rather than to exclude or confirm disease (odds ratio 0.3, 95% confidence interval 0.1 to 0.6). This effect was independent of the results of the x-ray examinations. CONCLUSION: Physicians seem to be aware that they have requested spinal x-ray examinations only to reassure patients, and they account for this in their management. These findings support debate on the negative consequences of requesting tests for other than purely medical reasons. Concerns about unjustified actions based on the results of x-ray examinations that were requested primarily to reassure patients should probably have only a minor role in the debate about unnecessary testing.